Erythroblast Enucleation - Keerthivasan, Ganesan (SAGE-Hindawi Access to Research, 2011)
Even though the production of orthochromatic erythroblasts can be scaled up to fulfill clinical requirements, enucleation remains one of the critical rate-limiting steps in the production of transfusable red blood cells. Mammalian erythrocytes extrude their nucleus prior to entering circulation, likely to impart flexibility and improve the ability to traverse through capillaries that are half the size of erythrocytes. Recently, there have been many advances in our understanding of the mechanisms underlying mammalian erythrocyte enucleation. This review summarizes these advances, discusses the possible future directions in the field, and evaluates the prospects for improved ex vivo production of red blood cells.